2011
DOI: 10.1051/0004-6361/201116437
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the energetics and evolution of dust withSpitzer: a chapter in the history of the Eagle Nebula

Abstract: Context. The Spitzer GLIMPSE and MIPSGAL surveys have revealed a wealth of details about the Galactic plane in the infrared (IR) with orders of magnitude higher sensitivity, higher resolution, and wider coverage than previous IR observations. The structure of the interstellar medium (ISM) is tightly connected to the countless star-forming regions. We use these surveys to study the energetics and dust properties of the Eagle Nebula (M 16), one of the best known star-forming regions. Aims. We present MIPSGAL obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
8
31
0
Order By: Relevance
“…the ∼10,000 X-ray sources detected as young stars clearly belong to two distinct, equally numerous groups: (i) a clustered population, with centrally concentrated distributions of stars (including cases of "clusters of clusters"), and a fairly homogeneous distributed fainter population. This is consistent with two main modes of star formation: localized cluster formation from dense molecular cores, and more widely spread star formation from smaller condensations (e.g., "pillars" eroded by the hydrodynamical feedback from winds and/or supernova explosions from massive stars (M ⋆ > 8M ⊙ ), as in the Eagle Nebula (Guarcello et al 2010;Flagey et al 2011). The various clusters, as well as the distributed young stars in Carina nebula, also show a large spread in ages (∼1-10 Myr depending on the location within the nebula).…”
Section: Introductionsupporting
confidence: 56%
“…the ∼10,000 X-ray sources detected as young stars clearly belong to two distinct, equally numerous groups: (i) a clustered population, with centrally concentrated distributions of stars (including cases of "clusters of clusters"), and a fairly homogeneous distributed fainter population. This is consistent with two main modes of star formation: localized cluster formation from dense molecular cores, and more widely spread star formation from smaller condensations (e.g., "pillars" eroded by the hydrodynamical feedback from winds and/or supernova explosions from massive stars (M ⋆ > 8M ⊙ ), as in the Eagle Nebula (Guarcello et al 2010;Flagey et al 2011). The various clusters, as well as the distributed young stars in Carina nebula, also show a large spread in ages (∼1-10 Myr depending on the location within the nebula).…”
Section: Introductionsupporting
confidence: 56%
“…This emission could either originate from small stochastically heated particles, often referred to as very small grains (VSGs), or big grains (BGs) in thermal equilibrium with the radiation field (e.g., Paladini et al 2012). Whereas several authors attribute the 24 µm emission inside ionized regions to the increase of VSGs compared with BGs (Paradis et al 2011;Flagey et al 2011), the analysis of the IR arc in IC 434 revealed that the increased heating by stellar photons from the nearby stars, σ Ori AB, can explain the MIR emission (Ochsendorf et al 2014). Here, we sidestep this problem and note that the emission from 24 µm and Hα/radio throughout the bubble interiors shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Flagey et al (2011) have measured dust spectral energy distributions (SEDs) thanks to Spitzer data. They show that the SED cannot be accounted for by interstellar-dust heating by UV radiation, but an additional source of radiation is needed to match the mid-infrared flux.…”
mentioning
confidence: 99%